Promoting Good Governance with Social Funds and Decentralization - Parker, Andrew (World Bank, Washington, DC, 2012)
Bad governance undermines development. Two important types of World Bank support for local governance are social funds and broadly based support for governments committed to decentralizing responsibility and power to local governments and other local institutions. But there are concerns that these two approaches, which address different elements of governance, sometimes work at cross-purposes. A study was therefore commissioned to examine the interaction between social funds and decentralization in Bolivia and Honduras (advanced decentralization), Peru and Zimbabwe (some decentralization), and Cambodia, Malawi, and Zambia (little or no decentralization). This Note is based on the findings of the study.